Environmental sustainability indicators applied to bioprocesses: a bibliometric analysis (2005–2024) - Alviz-Meza, Anibal; Rojas-Flores, Segundo; González-Delgado, Ángel Darío (Frontiers in Chemical Engineering, 2025)
This study analyzes, quantifies, and maps, from a bibliometric perspective, the scientific production around environmental sustainability indicators used in bioprocesses covering the timeframe 2005–2024 in Scopus. Biblioshiny software in RStudio was used to categorize and evaluate the contributions of authors, countries, institutions, and journals. Their collaborative networks were also visualized using VOSviewer. The need to incorporate quantitative, qualitative, and descriptive indicators that comprehensively capture the environmental impacts of biotechnological processes led us to compile thirty diversified indices. The relevance of life cycle analysis as a fundamental tool is highlighted and triggered by integrating multicriteria analysis methods, optimization algorithms, and artificial intelligence. This combination of approaches allows for addressing the inherent complexity of evaluating systems that involve technical, environmental, economic, and social dimensions. Emerging trends point to a paradigm oriented towards the circular bioeconomy, where the diversification of flows in biorefineries and microalgae use are presented as key strategies to maximize efficiency and minimize environmental impacts. The synergy between traditional methodologies and advanced computational approaches constitutes the ideal framework to optimize the sustainability of bioprocesses, establishing a solid base for future research in this field.